Prevalence and factors associated with hepatitis B and D virus infections among migrant sex workers in Chiangmai, Thailand: A cross-sectional study in 2019 - Sayamon Hongjaisee (2020)
© 2020 The Author(s) Objectives: To determine the prevalence of hepatitis B surface antigen (HBsAg) and antibody to hepatitis delta virus (anti-HDV) and associated factors among migrant sex workers in Chiangmai, Thailand. Methods: This cross-sectional study was conducted at various sexual entertainment venues in Chiangmai, Thailand, in 2019. Consenting participants were interviewed using a questionnaire, and plasma was tested for hepatitis B virus (HBV) markers (DiaSorin, Italy) and anti-HDV antibody (DIA.PRO Diagnostic Bioprobes, Italy), if HBsAg-positive. Associations between HBsAg positivity or HDV antibody and potential factors were examined using univariable and multivariable logistic regression analysis. Results: A total of 396 migrant sex workers, half of them female, were recruited between February and September 2019. Their median age was 25 years (interquartile range 22–30 years) and 95% were Burmese. Overall, HBsAg prevalence was 11.4%; 8.1% in females and 14.7% in males (Chi-square, p = 0.040). One-third were still susceptible to HBV. No HBsAg-positive participants had anti-HDV antibodies. HBsAg positivity was associated with being male (adjusted odds ratio (aOR) 3.01, 95% confidence interval (CI) 1.25–7.68, p = 0.014), having attended school (aOR 4.50, 95% CI 1.26–15.98, p = 0.020), being separated/divorced/widowed (aOR 5.77, 95% CI 1.48–22.52, p = 0.012), and having unprotected sex (aOR 3.38, 95% CI 1.31–8.71, p = 0.012). Conclusions: In this young population, higher HBsAg prevalence in males may be related to sexual transmission, indicating the need for HBV screening programs linked with HBV prevention and care.